Penggunaan Analisis SWOT untuk Strategi Pemasaran dalam Meningkatkan Penjualan - Dewi Puspaningtyas Faeni; Jumawan Jumawan; Nazifa Fitri; Siti Wahdaniyah Putri; Mira Anggaina; Elisa Nabila Putri; Adelia Vita Arzety (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
The level of business competition that is getting tighter at this time makes business actors need to have a strategy so that the company can survive and develop. Companies need to implement a powerful marketing program or strategy to boost shoe sales in order to prepare themselves for the increasingly fierce competition from other competing businesses. By using SWOT analysis, a business can determine which ways need to be improved both inside and outside to ensure work operations run smoothly. This research method uses a literature review method with a qualitative descriptive writing system. Using relevant previous research totaling 8 journal articles. The results showed that in the marketing process cannot be separated from the use of SWOT analysis to be able to find out what are the strengths, weaknesses, opportunities, and threats for a small business unit such as MSMEs or companies, with SWOT analysis, companies are able to develop various strategies to market their products or services in order to increase sales volume. With this increase in sales, it is hoped that it will be able to continue to develop the company in a better direction.